2014
DOI: 10.3389/fnins.2014.00250
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of short-term memory in primate auditory cortex

Abstract: Behaviorally-relevant sounds such as conspecific vocalizations are often available for only a brief amount of time; thus, goal-directed behavior frequently depends on auditory short-term memory (STM). Despite its ecological significance, the neural processes underlying auditory STM remain poorly understood. To investigate the role of the auditory cortex in STM, single- and multi-unit activity was recorded from the primary auditory cortex (A1) of two monkeys performing an auditory STM task using simple and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 95 publications
4
31
1
Order By: Relevance
“…2), but delay activity was seldom selective for the preceding stimulus. Similar results have been reported in the caudal belt [23], dorsal temporal pole (our TGd; [28]), and recently in AI [29]. Our serial DMS paradigm revealed that while DS persisted throughout the trial, DE was not robust to interference, and diminished in tandem with behavioral accuracy (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…2), but delay activity was seldom selective for the preceding stimulus. Similar results have been reported in the caudal belt [23], dorsal temporal pole (our TGd; [28]), and recently in AI [29]. Our serial DMS paradigm revealed that while DS persisted throughout the trial, DE was not robust to interference, and diminished in tandem with behavioral accuracy (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…The ME that we observed, which appeared 80-180 ms after stimulus onset, has not been described previously in auditory cortex; ME ≥300 ms after sound onset has been reported in AI and TGd [28, 29], but likely represents response selection and/or feedback from PFC [13]. By contrast, short-latency MS has been reported in AI (23% of units;[29]), caudal auditory belt (22%;[23]), and TGd (9%; [28]). Collectively these data argue against a specialization for STM at the temporal pole, and in favor of a more distributed representation that includes core and belt.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Recent studies have re-opened the question of how cortical neurons represent auditory STM in the nonhuman primate model (Fig 2; Bigelow et al, 2014; Ng et al, 2014; Plakke et al, 2013; Scott et al, 2014). As described above (section 2.2), Scott et al (2012; 2012; 2014) applied a serial DMS paradigm using stimuli and delays of a similar duration to those of Gottlieb et al (1989) but with two key differences: stimuli comprised a range of acoustic categories, and intervening nonmatch stimuli could appear between the sample and match (Fig.…”
Section: Cortical Systems For Auditory Stmmentioning
confidence: 99%
“…Part of the recorded region was co-extensive with the rostral superior temporal gyrus lesion applied by Fritz et al (2005; see section 2.1), which reduced forgetting thresholds from 30–50 s to <10 s, implicating this region in supporting auditory DMS. A complementary set of studies from Poremba and colleagues recorded from areas bracketing the rSTC at lower and higher stages of cortical processing: the primary auditory cortex (AI; Bigelow et al, 2014), and the dorsal temporal pole (dTP: Ng et al, 2014), as well as the dorsolateral PFC (Plakke et al, 2013). The following sections (3.1–3.3) integrate these findings to outline a temporal-frontal network engaged during auditory STM in the nonhuman primate.…”
Section: Cortical Systems For Auditory Stmmentioning
confidence: 99%